ANALYZING STUDENTS’ COMPETENCE IN VOCABULARY MASTERY THROUGH ONLINE GAME “PUBG” (PLAYERS’ UNKNOWN BATTLE GROUNDS) TO THE 2ND GRADE STUDENTS AT MADRASAH ALIYAH NEGERI 1 SANANA - Amrin Hi. Saban; Faujia Umasugi; Zakiah Buamona (JURNAL DODOTO, 2021)
PUBG as an online game that has many English terms in it. Playing it repeatedly can allow the player to remember the vocabulary. Students can use online game not only as a medium for entertainment but also as a medium for learning English that can increase students’ vocabulary. Therefore, the researcher did this research in order to know how far the students’ vocabulary mastery through online game PUBG at MAN 1 Sanana. The design of this research was a descriptive research. This research aimed at knowing the extent of students’ competence in mastering vocabulary through online game. The samples of this research were from the second, grade students of MAN 1 Sanana amounted to 25 students. They are the PUBG players. Firstly, the students were tested and then the researcher interviewed the students to know their pattern to play this game. In colleting the data there were question sheets which have 50 items about vocabulary consist in the PUBG game. The result of the research showed that the students’ competence in vocabulary mastery through online game PUBG at Madrasa AliyahNegeri 1 Sanana is in the good category. Dealing with the score that the students got, it can be seen from the result of the test, that is 66,52 %